Light transmissivity of tube shelters affects root growth and biomass allocation of Quercus ilex L. and Pinus halepensis Mill - de Castro, Alberto Vázquez; Oliet, Juan A.; Puértolas, Jaime; Jacobs, Douglass F.; Puértolas, Jaime; Jacobs, Douglass F. (ANNALS OF FOREST SCIENCE, 2014)
Context Tube shelters have been shown to enhance field performance of several Mediterranean species, but responses of newly planted seedlings to the microenvironment induced by shelter walls with different light transmissivity are still poorly documented. Aims We studied effects of a range of shelters with varying light transmissivity on post-planting seedling responses during the wet season establishment phase for two Mediterranean trees of contrasting functional ecology. Methods Root growth, biomass allocation, water potential, and chlorophyll fluorescence of Quercus ilex and Pinus halepensis seedlings were evaluated across shelters varying in light transmissivity (80, 40, 20, and 10 % plus a mesh shelter) with irrigation. Results Plants in dark tubes (20 and 10 % light transmissivity) had less above-and belowground growth and more than two times greater leaf to protruding roots mass ratio, with shoot growth response of Q. ilex being less plastic. Ratio of leaf area/protruding roots area decreased when light transmissivity increased, although no differences were found at >= 40 % transmissivity. Xylem water potential indicated lack of water stress, and high maximum photosynthetic efficiency (F-v/F-m) values show no photoinhibition symptoms irrespective of light transmissivity. Conclusion Shelter transmissivity >= 40 % promotes rapid and vigorous root growth immediately after planting for these species. This minimum transmissivity should be considered as a target when designing shelters to help root development and improve water balance of Mediterranean seedlings.
Keywords: Aleppo pine; chlorophyll fluorescence; Forest restoration; Holm oak; Light ambient response; Mediterranean climate; Transplanting performance; Treeshelters